TERRORISM IN INTERNATONALCRIME - Shafira Tri Pinareswati. Fira.; Miliarni Deida Navydien, Navy; Khesya Khusnul F. U khesya; Annisa Amalia Ramadhani Annisa (Universitas Duta Bangsa Surakarta, 2023)
Terrorism is a form of crime that is included in the extraordinary crime which in its legal settlement requires special handling. The crime of terrorism is a crime that is feared by the world community, including Indonesia, because the characteristics of this crime are to create a sense of insecurity and spread terror to society and the victims of this crime of terrorism feel that until now they have not received full justice. In Indonesia there have been many acts of terrorist group attacks that have succeeded in destabilizing security and government. The act of terrorism first occurred in Indonesia, which is known as the incident Bom Bali I in year 2022. The focus of this study on legal writing is to discuss the extent to which the effectiveness of UU No. 31 Tahun 2004 in providing protection to victims of criminal acts of terrorism. The writing of this law is a normative legal research using the literature study method to resolve legal issues in an effort to provide protection for victims due to criminal acts of terrorism that occurred in Indonesia which are then analyzed using related laws and regulations. The result of writing this law is the need for protection and a sense of justice for victims of criminal acts of terrorism and also the role of law enforcers is needed to uphold justice and the role of the government in terms of being able to provide fair compensation for victims affected by acts of terrorism.